PATHOLOGICAL ANATOMY OF THE THYROID GLAND IN WOMEN WITH CEREBRAL INJURIES (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
Traumatic brain injury (TBI) is an important pathological factor leading to dysfunction of the neuroendocrine system in women.In particular, the thyroid gland (TH) is closely connected to the central nervous system through the hypothalamic-pituitary axis and is characterized by a rapid response to hormonal imbalance and morphofunctional changes in women after head injuries. Due to the high sensitivity of the endocrine system in the body of injured women, the study of pathological anatomical changes that occur in the uterus after UTI is of great scientific and practical importance.